2017
DOI: 10.1016/j.tranpol.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected versus expected network disruption: Effects on travel behavior

Abstract: This paper discusses the observed evolution of traffic in the Minneapolis-St Paul (Twin Cities) region road network following the unexpected collapse of the I-35W Bridge over the Mississippi River. The observations presented within this paper reveal that traffic dynamics are potentially different when a prolonged and unexpected network disruption occurs rather than a preplanned closure. Following the disruption from the I-35W Bridge's unexpected collapse, we witnessed a unique trend: an avoidance phenomenon af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…This section details our analysis of the switching behavior of respondents. Switching behavior refers to the tendency of respondents to change their transportation mode after a disruption (Di et al, 2017;Danczyk et al, 2017), such as the stay-at-home order in New York City in this study. Since respondents were allowed to record multiple modes of transportation, a respondent was labeled as a switcher if they changed one of their transportation modes from before the stay-athome order to after the stay-at-home order.…”
Section: Switching Behaviormentioning
confidence: 99%
“…This section details our analysis of the switching behavior of respondents. Switching behavior refers to the tendency of respondents to change their transportation mode after a disruption (Di et al, 2017;Danczyk et al, 2017), such as the stay-at-home order in New York City in this study. Since respondents were allowed to record multiple modes of transportation, a respondent was labeled as a switcher if they changed one of their transportation modes from before the stay-athome order to after the stay-at-home order.…”
Section: Switching Behaviormentioning
confidence: 99%
“…Recently, studies have examined the optimization of traffic signal timings as an active management tool for nonrecurring congestion (3)(4)(5)(6). Traffic assignment models, equipped with behavior models that characterize travelers' behavior changes after incidents, and predictioncorrection models are often built to simulate the timedependent diverted traffic flow under pre-defined incident scenarios (7)(8)(9)(10)(11)(12)(13). The signal timings, optimized for a given incident scenario, then favor specified directional movements to minimize the induced congestion (14).…”
Section: Traffic Signal Timings For Incident Managementmentioning
confidence: 99%
“…However, evidence shows that some passengers tend to avoid the location of a failed infrastructure element completely even though there may still be capacity available (e.g. partially closed due to a slope failure) due to the perception of a safety risk [5]. Besides switching to another route, changing departure time is also often reported.…”
Section: Passenger Transport During Disruptionsmentioning
confidence: 99%
“…The behavioural responses mentioned in the previous sections are likely to result in a new equilibrium of traffic flows. However, evidence shows that this may take several weeks [5] due to habitual patterns and routines. Evidence has also shown that disruptions tend to lead to overreactions in passenger behaviour [4], leading to oscillating traffic among several routes (e.g.…”
Section: Day-to-day Variabilitymentioning
confidence: 99%